Pengaruh Budaya Organisasi dan Insentif Finansial terhadap Semangat Kerja Pegawai (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The purpose of this study was to find out how organizational culture and financial incentives impact staff morale at Puskesmas Kerambitan I in Tabanan Regency. In Sembung Gede Village, Kerambitan District, Tabanan Regency, Puskesmas Kerambitan I is the location of this study. This study collected quantitative and qualitative data. This study involved 64 employees from Puskesmas Kerambitan I in Tabanan Regency. The sampling method uses a saturated sampling technique. Multiple linear regression analysis, significant t-test, and significant F-test are used to analyze the data. This study found that organizational culture at Puskesmas Kerambitan I in Tabanan Regency influenced employee morale positively and significantly. Employees of Puskesmas Kerambitan I in Tabanan Regency feel the positive impact of financial incentives. Organizational culture and financial incentives have a significant effect simultaneously on morale in employees of Puskesmas Kerambitan I in Tabanan Regency. It is recommended that the Kerambitan I Health Center in Tabanan Regency routinely hold evaluations at the end of every month and breafing morning